Polarization transfer by cross-correlated relaxation in solution NMR with very large molecules - Riek, Roland (The National Academy of Sciences, 1999)
In common multidimensional NMR experiments for studies of biological macromolecules in solution, magnetization transfers via spin–spin couplings [insensitive nuclei enhanced by polarization transfer (INEPT)] are key elements of the pulse schemes. For molecular weights beyond 100,000, transverse relaxation during the transfer time may become a limiting factor. This paper presents a transfer technique for work with big molecules, cross relaxation-enhanced polarization transfer (CRINEPT), which largely reduces the size limitation of INEPT transfers with the use of cross-correlated relaxation-induced polarization transfer. The rate of polarization transfer by cross-correlated relaxation is proportional to the rotational correlation time, so that it becomes a highly efficient transfer mechanism for solution NMR with very high molecular weights. As a first implementation, [(15)N,(1)H]-correlation experiments were designed that make use of cross-correlation between dipole–dipole coupling and chemical shift anisotropy of the (15)N—(1)H-moieties for both CRINEPT and transverse relaxation-optimized spectroscopy (TROSY). When compared with INEPT-based [(15)N,(1)H]-TROSY, these experiments yielded up to 3-fold signal enhancement for amide groups of a 110,000-Da protein in aqueous solution at 4°C. CRINEPT opens avenues for solution NMR with supramolecular structures such as membrane proteins solubilized in micelles or lipid vesicles, proteins attached to nucleic acid fragments, or oligomeric proteins.